Tumor antigens heterogeneity and immune response-targeting neoantigens in breast cancer. (July 2021) - Benvenuto, Monica; Focaccetti, Chiara; Izzi, Valerio; Masuelli, Laura; Modesti, Andrea; Bei, Roberto
Abstract: Breast cancer is both the most common type of cancer and the most frequent cause of cancer mortality in women, mainly because of its heterogeneity and limited immunogenicity. The aim of specific active cancer immunotherapy is to stimulate the host's immune response against cancer cells directly using a vaccine platform carrying one or more tumor antigens. In particular, the ideal tumor antigen should be able to elicit T cell and B cell responses, be specific for the tumor and be expressed at high levels on cancer cells. Neoantigens are ideal targets for immunotherapy because they are exclusive to individual patient's tumors, are absent in healthy tissues and are not subject to immune tolerance mechanisms. Thus, neoantigens should generate a specific reaction towards tumors since they constitute the largest fraction of targets of tumor-infiltrating T cells. In this review, we describe the technologies used for neoantigen discovery, the heterogeneity of neoantigens in breast cancer and recent studies of breast cancer immunotherapy targeting neoantigens.